Variação espacial de atributos do solo, em zona de recarga de nascente, em uma microbacia perene do semiárido - Ferreira, Larissa Luana Nicodemos (Universidade Federal Rural do Semi-Árido, 2016)
Because of population growth, increasingly accentuated the need for the use of natural resources, especially soil and water and can lead to degradation thereof, and the study of the attributes of the fundamental soil in the design and understanding of human impacts on the environment. Then, describe and map the land use and occupation with the spatial variability of its attributes is very important to put into practice the rational and proper management of exploitation of these resources. Therefore, the objective of this study was to map the use and occupation of land along with their physical-water and chemical attributes, using Geographic Information System and geostatistics, a spring recharge area of a perennial watershed shed in semi-arid conditions. The study area is inserted in the middle course of the river basin of Apodi-Mossoró River, located in the west of Rio Grande do Norte state, soil samples were taken at various points of the study area for the characterization and mapping of attributes evaluated. The use of geostatistics, coupled with the Geographic Information System, proved to be feasible for the spatial distribution of soil properties, contributing significantly to a more precise mapping of the attributes studied. The results indicated that the physical water soil attributes were less variable and more stable to human activities in the area, when compared to chemical attributes. In addition, the local vegetation, topography and relief interfered directly in the behavior of soil properties (chemical and physical water). The results showed a close relationship between the use and occupation of land and the spatial distribution of its attributes, indicating the impact of different human actions on the environment. Thus, it was possible to identify areas that should be preserved (springs, hill top, recharge areas, etc.), but are manejas and its natural conditions modified by human action. Thus, it is concluded that the spatial measurement of human impacts on the environment is crucial step for planning the use and occupation in a rational way, adopting conservation techniques of natural resources
Keywords: Hidrologia; Bacia Apodi-Mossoró; Caatinga; Hydrology; Basin Apodi-Mossoró; Caatinga; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO